2018
DOI: 10.1021/jacs.8b01072
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale Metal–Organic Framework Overcomes Hypoxia for Photodynamic Therapy Primed Cancer Immunotherapy

Abstract: Immunotherapy has become a promising cancer therapy, but only works for a subset of cancer patients. Immunogenic photodynamic therapy (PDT) can prime cancer immunotherapy to increase the response rates, but its efficacy is severely limited by tumor hypoxia. Here we report a nanoscale metal-organic framework, Fe-TBP, as a novel nanophotosensitizer to overcome tumor hypoxia and sensitize effective PDT, priming non-inflamed tumors for cancer immunotherapy. Fe-TBP was built from iron-oxo clusters and porphyrin lig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
367
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 597 publications
(371 citation statements)
references
References 26 publications
2
367
0
2
Order By: Relevance
“…[17] Thet ransmission electron microscopy (TEM) images revealed that the NMOF has au niform nanoshuttle morphology with the sizes of about 258 AE 43 nm in length and 96 AE 13 nm in width ( Figure 1a;see Figure S1 in the Supporting Information). [17] Thet ransmission electron microscopy (TEM) images revealed that the NMOF has au niform nanoshuttle morphology with the sizes of about 258 AE 43 nm in length and 96 AE 13 nm in width ( Figure 1a;see Figure S1 in the Supporting Information).…”
mentioning
confidence: 99%
“…[17] Thet ransmission electron microscopy (TEM) images revealed that the NMOF has au niform nanoshuttle morphology with the sizes of about 258 AE 43 nm in length and 96 AE 13 nm in width ( Figure 1a;see Figure S1 in the Supporting Information). [17] Thet ransmission electron microscopy (TEM) images revealed that the NMOF has au niform nanoshuttle morphology with the sizes of about 258 AE 43 nm in length and 96 AE 13 nm in width ( Figure 1a;see Figure S1 in the Supporting Information).…”
mentioning
confidence: 99%
“…For example, Liu et al have used the mixture of methanol and DMF as solvent to construct nanoscale NH 2 ‐MIL‐125(Ti) through the interaction between Ti(OC 4 H 9 ) 4 and NH 2 ‐BDC (BDC: 1,4‐benzenedicarboxylic acid) in an airtight reactor at 150 °C within 24 h . Lin and co‐workers have chosen a solvent containing DMF and formic acid (FA) to synthesize Fe‐TBP nanorice with the length of 100 nm (TBP: 5,10,15,20‐tetra( p ‐benzoato)porphyrin) by the reaction between [Fe 3 O(OAc) 6 (H 2 O) 3 ]OAc (OAc = acetate) and H 4 TBP at 80 °C for 24 h . In addition to choosing different solvents, their concentration or the ratio of the mixed solvents is also crucial, which may affect the morphology of the synthesized products.…”
Section: Synthesismentioning
confidence: 99%
“…a) Nanorice morphology of Fe‐TBP. Reproduced with permission . Copyright 2018, American Chemical Society.…”
Section: Biocompatibilitymentioning
confidence: 99%
See 2 more Smart Citations